PERBANDINGAN FRAKSI VOLUME KOMPOSIT CARBON TOW/EPOXY ANTARA METODE MANUFAKTUR VACUUM INFUSION DENGAN FILAMENT WINDING - Ramadhan, Fahri; Hestiawan, Hendri; FA, A. Sofwan; Purnomo, Herry (UNIB Press, 2023)
Several methods can be applied in composite manufacturing, including the vacuum infusion and filament winding methods. In order to apply this method in the manufacture of composites, it is necessary to know which produces composites with a good target ratio of fiber and resin, namely 60%/40%. The aim of this research is to compare the manufacturing methods that produce the distribution of fibers and resins that are close to the target. The composites in this study used a carbon tow reinforcement material with a matrix, namely araldite LY5052 epoxy resin and aradur 5052 CH hardener. In composite manufacturing, there are three stages, namely molding preparation, process manufacturing, and demolding. Then SEM photo observations were made on the specimen pieces from the composite results with three different locations. Of the two methods, vacuum infusion produces SEM photos with denser fiber distribution than filament winding and voids produced in the filament winding manufacturing method. The volume fraction of the test on the vacuum infusion sample with an average yield of 56.79% and 54.01% for filament winding.